HAWALAH MUTHLAQAH DALAM PERSPEKTIF SYAFI ‘IYAH DAN HANAFIYAH - Mariana Mariana; Amsanul Amri (Koordinator Perguruan Tinggi Agama Islam (KOPERTAIS) Wilayah V Aceh, 2020)
This study aims to understand the concept of muthlaqah debt transfer according to Syafi’iyah and Hanafiyah and to find out the similarities and differences between muthlaqah and Shayfiyah and Hanafiyah. The results of the study show that the acquisition of muthlaqah according to Syafi’iyah is an unauthorized transfer of debt as compensation from the payment of muhil debt to muhal and that muthlaqah is not allowed. The transfer of muthlaqah debt according to Hanafiyah means that if the transfer is in the form of muthlaqah then the two debts must not be the same, both in quantity and quality, and the transfer of muthlaqah debt is allowed. There is a difference of opinion between the transfer of muthlaqah debt according to Hanafiyah when the transfer is in the form of a transfer of muthlaqah debt so the two debts do not have to be the same, in both quantity and quality, the transfer of muthlaqah debt is allowed. However, according to Syafi’iyah if there is a difference in the amount (debt in money) or quality difference (debt in the form of goods) then the transfer of muthlaqah debt is invalid. The Shiafi'iyah scholars argue that the two debts must be equal between the expiration dates, otherwise they are invalid.